CAIO GRACO AND HIS RELATIONSHIP WITH THE EQUITES (1st century BC): A BRIEF ANALYSIS OF APIAN OF ALEXANDRIA’S INTERPRETATION (2nd century AD) - Souza, Alice Maria de (Revista Archai, 2010)
We propose here an analysis of the Apiano's de Alexandria report about the relation between Caio Graco and the equestrian order in the end of the century II B.C. Apiano wrote his Civil Wars on the end of his life, during the reign of Marco Aurélio, in a time of internal peace, stability and expansion. In his report, Apiano shows friendliness for the reformist project of Caio Graco, and does an analysis about the transfer of power in the courts to the members of the equestrian order, did by an younger Graco in the end of Roman Republic. (II B.C)